Tidal Effects on the Flow and Channel Geometry of Klang River Estuary - Mahdi, Muhannad A. (2000)
The aim of this study is to predict the long-term behaviour of the Klang River estuary in terms of changes in the river morphology due to tidal effect that will help plan the industrial and commercial activities within the estuaries. The main objectives were to simulate the tidal effect on channel geometry, and the flow (water level) by using a mathematical modelling of finite difference approach (MIKE 11) as well as analysis of available data. The input data for MIKE 11 was the tide water level at port Klang and the probable discharge at Kota Bridge for ARI1OO, 70,50,10 from previous report and the cross section for 1993 survey. Changes in river morphology were evaluated by dividing Klang River estuary into five sections based on the available data for the cross section throughout the year. Soil investigation was also carried out to determine the soil properties in order to study the behaviour of the estuary. The findings show that water level at the end of the study area (Kota Bridge) was subjected to high and low water level with the same sequence as in Port Klang, and the ARI 100 flood capacity could be achieved if the amount of sediment load entering the estuary from upstream due to river improvement work was controlled. The grain size diameter was obtained by using the hydrometer analysis from two locations in the estuary and d50 was found to be an average between 0.006mm-0.008mm. Simulated flows using MIKE11 software gave tidal discharge of 2000m3/sec. The study also showed that there was a decrease in v01ume of flow by 40% below Kota Bridge between Section-1 to Chainage 15900m and between Chainage 300m to Chainage 3200m from the river mouth, in the other hand there was a 20 %. Decrease in channel capacity between Chainage 3200m to Chainage 15900m. The estuary is considered a well-mixed estuary and the water depth are more than 3m that made it suitable for navigation. The study recommended the use of hydraulic sluicing, agitation dredging and tidal flushing to reduce sedimentation. It is recommended to set up a permanent station at Kota Bridge that can measure hourly discharge, water level, velocity, and suspended solids that pass through the above section.